PESAN FOTO JURNALISTIK PELANGGARAN SYARIAT ISLAM DI ACEH: (Analisis Semiotika Foto Pada Website Menatapaceh.com Harian Serambi Indonesia) - Ismail Arafah; Junaidi (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2017)
The focus in this study is to examine how does the meaning of photo jurnalism about the violation of Islamic Shari'ah that presented on the website Menatapaceh.com. The research is used descriptive qualitative method, which is discussing some photojournalism study with Roland Barthes semiotics analysis theory which is refers to some signs (denotation, connotation and myth). The photo for research sample is taken from the Menatapaceh.com which is have 6 (six) photos. Denotation on those six photos show us a clear meaning. But in terms of connotation there is not all photos have the six semiotics procedures of Roland Barthes connotation, there are only a few procedures that shown such as trick effect, object and photogenia. That is seen in some images is have cropping frames of some photos, color settings and lighting on the camera. The way photographers take the pictures is simplified, that make easy for readers to understand the messages contained in the photos. The true meaning of a photos is only know by the photographer himself. In that photojournalism which is found on the website Menatapaceh.com all contain three elements of Roland Barthes semiotics theory it's the denotation, connotation and myth.